Patients With Chronic Hepatitis C Virus Infection Are at an Increased Risk of Colorectal Cancer: A Nationwide Population-Based Case-Control Study in Taiwan - Su, Fu-Hsiung; Bai, Chyi-Huey; Le, Thi Nga; Muo, Chih-Hsin; Chang, Shih-Ni; Te, Arlene; Sung, Fung-Chang; Yeh, Chih-Ching (Frontiers in Oncology, 2021)
Aim Studies evaluating colorectal cancer (CRC) risk associated with chronic hepatitis C virus (HCV) infection are limited. Methods In this case-control study, we identify 67,670 CRC cases newly diagnosed from 2005 to 2011 and randomly selected 67,670 controls without HCV and CRC from the same database, frequency matched by age and sex of cases. Results Results of logistic regression analysis revealed that the adjusted odds ratio (aOR) of CRC was 1.16 (95% confidence interval [CI] = 1.08–1.24, p < 0.001) in association with chronic HCV. The CRC risk was slightly greater for women than for men. The risk decreased with age, with the aOR decreased from 2.26 (95% CI = 1.32–3.87, p = 0.003) in patients under 45 years old to 1.31 (95% CI = 1.10–1.55, p = 0.03) in patients aged 50–59, and 1.10 (95% CI = 1.00–1.22, p = 0.061) in patients aged over 70. Conclusions Our findings suggested that patients with chronic HCV infection are at an elevated risk of developing CRC. Our data also imply that the CRC prevention programs are needed to target younger HCV patients.